1999
DOI: 10.1093/emboj/18.10.2702
|View full text |Cite
|
Sign up to set email alerts
|

PrP-dependent association of prions with splenic but not circulating lymphocytes of scrapie-infected mice

Abstract: An intact immune system, and particularly the presence of mature B lymphocytes, is crucial for mouse scrapie pathogenesis in the brain after peripheral exposure. Prions are accumulated in the lymphoreticular system (LRS), but the identity of the cells containing infectivity and their role in neuroinvasion have not been determined. We show here that although prion infectivity in the spleen is associated with B and T lymphocytes and to a lesser degree with the stroma, no infectivity could be detected in lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
2
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 32 publications
7
67
2
1
Order By: Relevance
“…In mice, thymus accumulates infectivity very early after the infection by introduction of the scrapie agent into various peripheral sites (41,42), and Muramoto et al (43) have shown the presence of PrP sc in the thymus of mice infected with the agent of Creutzfeldt-Jakob disease (CJD). The thymus is devoid of both B lymphocytes and follicular dendritic cells, which have been claimed to support the initial replication of the scrapie agent (25,(44)(45)(46). Thus, our data support the hypothesis that epithelial cells could accumulate or replicate prions in the thymus and could provide an interface between the lymphoreticular system and the peripheral nerves that permit neuroinvasion to occur.…”
Section: Discussionsupporting
confidence: 81%
“…In mice, thymus accumulates infectivity very early after the infection by introduction of the scrapie agent into various peripheral sites (41,42), and Muramoto et al (43) have shown the presence of PrP sc in the thymus of mice infected with the agent of Creutzfeldt-Jakob disease (CJD). The thymus is devoid of both B lymphocytes and follicular dendritic cells, which have been claimed to support the initial replication of the scrapie agent (25,(44)(45)(46). Thus, our data support the hypothesis that epithelial cells could accumulate or replicate prions in the thymus and could provide an interface between the lymphoreticular system and the peripheral nerves that permit neuroinvasion to occur.…”
Section: Discussionsupporting
confidence: 81%
“…It is not clear, however, which immune system : I I:: cells play a key role in pathogenicity. Spleen fractionation studies have shown that infectivity is associated with the stromal fraction and with lymphocytes (Clarke and Kimberlin, 1984;Raeber et al, 1999). The incubation period in peripherally infected mice is unaffected by whole body irradiation (Fraser and Farquhar, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Both nervous and immune systems have one of the identified cellular requirements for the replication of the TSE's agent that is cellular PrP expressing cells (Brandner et al, 1996;Btieler et al, 1993;Horiuchi et al, 1995;McBride et al, 1992). Within lymphatic tissues the germinal centre microenvironment has been more particularly incriminated in peripheral prion replication with the implication of B lymphocytes / follicular dendritic cells (FDCs) (Kitamoto et al, 1991;Klein et al, 1997;Raeber et al, 1999a;Raeber et al, 1999b). How TSE's agent propagates from lymphatic tissues to Central Nervous System (CNS) is unclear but autonomic nerve system that innervates the lymphoid organs may contribute to their dissemination from the spleen to the CNS (Fried et al, 1986).…”
Section: Introductionmentioning
confidence: 99%